3D-microanatomy of a keystone planktonic species, the northern polar pteropod Limacina helicina helicina (Gastropoda: Heterobranchia). (18th January 2019) - Laibl, C F; Schrödl, M; Kohnert, P C
Abstract: We present the first full anatomical investigation of Limacina helicina helicina (Phipps, 1774), based on an adult from western Greenland. 3D-reconstruction of histological semi-thin serial sections was used to reconstruct all major organ systems. Anatomical differences between helicoid and straight-shelled thecosomes, and organ homologies with the putative sister group Anaspidea are summarized with regard to recent phylogenetic advances. Our results agree with the existing morphology-based taxonomy and contribute substantially to current knowledge on limacinid (micro-)anatomy.